Detection of α-thalassemia South-East Asian deletion based on a fully integrated digital polymerase chain reaction system DropXpert S6 - Youqiong Li; Junwei Ye; Liang Liang; Xiao Tan; Lihong Zheng; Ting Qin; Linfen Yu (Hematology)
Objectives: This study aimed to establish a droplet digital polymerase chain reaction (ddPCR) assay for South-East Asian (SEA) deletion based on a fully integrated digital PCR system DropXpert S6.Methods: A total of 151 whole blood samples, 10 chorionic villus samples, and 17 amniotic fluid samples were collected, including 106 SEA heterozygotes, 43 normal individuals, 10 Hb Bart's hydrops details, and 19 SEA deletions combined with other genotypes.Genotypes of these samples were determined by the Gap-PCR method. We perform a series of optimizations of the ddPCR system to ensure the performance of the entire ddPCR reaction, such as droplet stability, fluorescence clustering, sensitivity, and accuracy.Results: Our assay exhibited 99.4% (177/178) accuracy compared with the Gap-PCR method, and the minimum detection limit of DNA was 0.1 ng/μL.Both targets have reliable linearity, R2 = 0.9999 for the α-thalassemia SEA deletion allele and R2 = 1 for the wild-type allele. The coefficient of variation for α-thalassemia SEA deletion allele detection at 2 and 10 ng/μL concentrations was 5.42% and 1.91%, respectively. In contrast, the coefficient of variation for wild-type allele detection was 4.06% and 1.83%, demonstrating its high quantitative accuracy. In addition, the DropXpert S6 PCR system showed some advantages over other ddPCR instruments, such as reducing testing costs, simplifying and automating the workflow.Conclusions: The DropXpert S6 PCR system provided a highly accurate diagnosis for α-thalassemia SEA deletion and can be used to detect α-thalassemia as an alternative method.